2017
DOI: 10.1016/j.jenvp.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceived home is associated with psychological well-being in a cohort aged 67–70 years

Abstract: • Depressive mood and purpose in life are associated with a low control of home • Depressive mood is associated with low emotional and social attachment to home • High behavioural meaning of home is associated with feeling autonomous • The physical and social experience of home is associated with purpose in life • Perceptions about home must be considered when planning age-friendly communities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
(55 reference statements)
4
26
0
Order By: Relevance
“…The results of this study are congruent with previous findings showing associations between the external HCQ instrument and with ADL, life satisfaction, depression and psychological well-being [ 1 , 9 - 11 ]. As to convergent validity, our results are in agreement with the predefined hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are congruent with previous findings showing associations between the external HCQ instrument and with ADL, life satisfaction, depression and psychological well-being [ 1 , 9 - 11 ]. As to convergent validity, our results are in agreement with the predefined hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…The 16 items of the two sub-scales were later combined, with results suggesting sufficient internal consistency ( α = 0.72) [ 1 ]. Later studies have indicated associations between the external HCQ and ADL, life satisfactions, depression and psychological well-being [ 1 , 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to deepen the knowledge on HCB dynamics and their role in the complex ageing process, a general aim should therefore be to assess the role of HCB in relation to other potential moderators and/or mediators and their relative contributions. Given previous evidence that depressive symptoms are related to ADL capacity (Nyunt et al 2012) as well as less perceived control over the housing situation (Kylén et al 2017), adjustment to prior internalizing and/or externalizing mental health problems might be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Housing accessibility, defined as a relationship between the person's functional capacity and the demands of the physical environment (Iwarsson and Ståhl 2003), is an indicator of person-environment (P-E) fit (Lawton and Nahemow 1973;Lawton 1986), and is central along the process of ageing as it influences well-being (Kylén et al 2017;Iwarsson 2005). Housing accessibility influences activities of daily living (ADL), and the association becomes stronger with decreasing functional capacity in particular (Iwarsson 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation